Transactions on Computational Science II - Hutchison, David; Kanade, Takeo; Kittler, Josef; Yao, Yiyu Y; Wang, Guoyin (Lecture Notes in Computer Science, 2008)
This volume covers denotational mathematics for computational intelligence. It includes 12 papers that detail: foundations and applications of denotational mathematics, rough and fuzzy set theories, granular computing, and knowledge and information modeling.